2019
DOI: 10.1073/pnas.1821712116
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Fe-Si-O liquid immiscibility at deep Earth pressures

Abstract: SignificanceEarth's outer core is composed of a liquid iron alloy with up to 10% of unknown light elements, likely silicon, oxygen, sulfur, carbon, or hydrogen. The release of these light elements upon freezing of the solid iron inner core plays an important role in sustaining Earth's magnetic field, but the exact chemical makeup of the core is widely debated. In this paper, we perform high-pressure, high-temperature melting experiments and first-principles simulations on iron alloys containing silicon and oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 53 publications
1
29
3
Order By: Relevance
“…This is in contrast with a recent experimental and first-principle calculation study (Arveson et al, 2019) where SiO 2 exsolution was not observed but where the presence of Fe-Si and Fe-Si-O immiscible liquids was proposed. This is in contrast with a recent experimental and first-principle calculation study (Arveson et al, 2019) where SiO 2 exsolution was not observed but where the presence of Fe-Si and Fe-Si-O immiscible liquids was proposed.…”
Section: Sio 2 Exsolution and Immiscibility In The Fe-si-o Liquidcontrasting
confidence: 99%
See 3 more Smart Citations
“…This is in contrast with a recent experimental and first-principle calculation study (Arveson et al, 2019) where SiO 2 exsolution was not observed but where the presence of Fe-Si and Fe-Si-O immiscible liquids was proposed. This is in contrast with a recent experimental and first-principle calculation study (Arveson et al, 2019) where SiO 2 exsolution was not observed but where the presence of Fe-Si and Fe-Si-O immiscible liquids was proposed.…”
Section: Sio 2 Exsolution and Immiscibility In The Fe-si-o Liquidcontrasting
confidence: 99%
“…Partial RDFs and coordination numbers agree well with previously reported liquid structures and show no sign of SiO 2 clustering. Shorter (10 ps) simulations give the impression of immiscibility, and those durations are comparable to the ones (6 to 14 ps) used in Arveson et al (2019). Ternaries formed by ideal volume mixing of Fe-Si and Fe-O binaries have identical density and bulk sound velocity as those obtained in the calculated ternary, implying that equations of state of binary liquids (Fe-Si and Fe-O) can be used to obtain reliable equations of state of Fe-Si-O ternary alloys at core conditions.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…No evidence of atomic clustering (i.e., exsolution) is observed visually or in the RDF in any of the cells, suggesting that the 4 at% of alloying element is below their solubility limit in Fe at the V and T studied. In recent work, Arveson et al () have shown, however, that computations tend to require significantly larger concentrations of alloying elements than experiments to show exsolution.…”
Section: Methodsmentioning
confidence: 99%